Association of the Implementation of the Patient-Centered Medical Home with Quality of Life in Patients with Multimorbidity - Schuttner, Linnaea (J Gen Intern Med, 2019)
BACKGROUND: The patient-centered medical home (PCMH) has clinical benefits for chronic disease care, but the association with patient-reported outcomes such as health-related quality of life (HRQoL) is unexplored in patients with multimorbidity (two or more chronic diseases). OBJECTIVE: To examine if greater clinic-level PCMH implementation was associated with higher HRQoL in multimorbid adults. DESIGN: A retrospective cohort study. PARTICIPANTS: Twenty-two thousand ninety-five multimorbid patients who received primary care at 944 Veterans Health Administration (VHA) clinics. MAIN MEASURES: Our exposure was the Patient Aligned Care Team Implementation Progress Index (PI(2)) for the clinic in 2012, a previously validated composite measure of PCMH implementation. Higher PI(2) scores indicate better performance within eight PCMH domains. Outcomes were patient-reported HRQoL measured by the physical and mental component scores (PCS and MCS) from the Short Form-12 patient experiences survey in 2013–2014. Interaction of the outcomes with total hospitalizations and primary care visit count was also examined. Generalized estimating equations were used for main models after adjusting for patient and clinic characteristics. RESULTS: The cohort average age was 68 years, mostly male (96%), and had an average of 4.4 chronic diagnoses. Compared with patients seen at the lowest scoring clinics for PCMH implementation, care in the highest scoring clinics was associated with a higher adjusted marginal mean PCS (42.3 (95% CI 41.3–43.4) versus 40.3 (95% CI 39.1–41.5), P = 0.01), but a lower MCS (35.2 (95% CI 34.4–36.1) versus 36.0 (95% CI 35.3–36.8), P = 0.17). Patients with prior hospitalizations seen in clinics with higher compared with lower PI(2) scores had a 2.7 point greater MCS (95% CI 0.6–4.8; P = 0.01). CONCLUSIONS: Multimorbid patients seen in clinics with greater PCMH implementation reported higher physical HRQoL, but lower mental HRQoL. The association between PCMH implementation and mental HRQoL may depend on complex interactions with disease severity and prior hospitalizations. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-019-05429-1) contains supplementary material, which is available to authorized users.